2014
DOI: 10.1001/jamasurg.2014.1076
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy and Short-term Morbidity in Patients Undergoing Mastectomy With and Without Breast Reconstruction

Abstract: IMPORTANCE Neoadjuvant chemotherapy (NC) is increasingly being used in patients with breast cancer, and evidence-based reports related to its independent effects on morbidity after mastectomy with immediate breast reconstruction are limited. OBJECTIVE To determine the effect of NC on 30-day postoperative morbidity in women undergoing mastectomy with or without immediate breast reconstruction. DESIGN, SETTING, AND PARTICIPANTS All women undergoing mastectomy with or without immediate breast reconstruction f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 34 publications
2
38
0
Order By: Relevance
“…Previous studies have demonstrated that IBR (both autologous and alloplastic based reconstruction) has a favorable complication profile even in the setting of chemotherapy. [16][17][18][19][20] In one study of 163 patients, with 66% undergoing expander/implant reconstruction, the authors found no statistically significant differences in infection or postoperative wound complications comparing patients who received neoadjuvant and adjuvant chemotherapy. However, they did find the adjuvant treatment group to have the highest rate of infectious complications (44%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that IBR (both autologous and alloplastic based reconstruction) has a favorable complication profile even in the setting of chemotherapy. [16][17][18][19][20] In one study of 163 patients, with 66% undergoing expander/implant reconstruction, the authors found no statistically significant differences in infection or postoperative wound complications comparing patients who received neoadjuvant and adjuvant chemotherapy. However, they did find the adjuvant treatment group to have the highest rate of infectious complications (44%).…”
Section: Discussionmentioning
confidence: 99%
“…20 A large database study including 19 258 IBR patients deemed neoadjuvant chemotherapy safe in both tissue expander and autologous breast reconstruction. However, the authors combined all complication types into "postoperative morbidity" and so the impact on infection could not be assessed; in addition they only included neoadjuvant chemotherapy 30 days before the operation, as was pre-defined by the AmericanCollege of Surgeons-National Surgical Quality Improvement Program variable 19. A proposed mechanism for the lack of significance found in overall morbidity with the introduction of neoadjuvant chemotherapy was discussed by Abt et al19 in which the authors hypothesized that the use of neoadjuvant chemotherapy decreases the tumor size, reducing operation time, and hence the reduction in operation time could lead to decreased overall morbidity.Given that limited studies discuss the impact of neoadjuvant chemotherapy as it relates to autologous reconstruction, and the one significantly powered study by Abt et al 8 grouped all complications together, our next aim was to sub-group by reconstructive type.…”
mentioning
confidence: 99%
“…For example, in a study including 3,696 patients with breast cancer who underwent NACT followed by mastectomy with or without immediate breast reconstruction, no increase in 30-day morbidity was observed compared to more than 60,000 women who underwent initial surgery. 38 …”
Section: Surgical Issuesmentioning
confidence: 99%
“…There have been a limited number of studies evaluating complication rates in patients undergoing NAC followed by SSM or NSM with IR, with conflicting results demonstrated. [21][22][23][24][25][26][27] Several studies have demonstrated no increased risk in patients having immediate reconstruction following NAC. 21,[24][25][26][27] On the other hand, others have reported very high complication rates in this setting.…”
Section: Rates Of Lrr In Patients With Smaller Tumors Have Been Repormentioning
confidence: 99%
“…[21][22][23][24][25][26][27] Several studies have demonstrated no increased risk in patients having immediate reconstruction following NAC. 21,[24][25][26][27] On the other hand, others have reported very high complication rates in this setting. 22,23 In A strength of this study is that we report on a large wellcharacterized patient group with longitudinal review of both shortterm as well as long-term complications and oncologic outcomes.…”
Section: Rates Of Lrr In Patients With Smaller Tumors Have Been Repormentioning
confidence: 99%